Wireless condition monitoring of a marine gearbox. Issue 1 (2nd January 2016) - Schirrmacher, S.; Overmeyer, L.; Lorisch, S.
Abstract : The condition-based maintenance of a marine gearbox poses special challenges because of the inaccessibility to the hull of the ship and harsh environment in the form of higher temperatures, continuous vibrations and salty sea air, which can lead to corrosion. In this article, the integration of a wireless sensor network with a marine gearbox is shown. The integration consists of sensor nodes that record characteristic measurement data, send them actively to a receiving unit and harvest energy from the environment for electrical supply after a one-time installation expenditure. The developed sensor node has a thermoelectric power supply that allows measurement intervals of less than 20 minutes. The recorded vibration data from the gearbox surface are sent via ZigBee wireless technology. By evaluating the envelope spectrum of the measured vibration data, the current rotational speed of the input drive shaft could be identified.